EVALUATING METHODS’ APPLICATION OF COMPLEX SYSTEMS’ EFFECTIVENESS IN THE AUTOMOBILE PASSENGER TRANSPORT THEORY - S. M. Mochalin; M. E. Kasper (Вестник СибАДИ)
Introduction. The article determines the relevance of the scientifically sound solutions and effective tools’ development in the evaluation of the passenger companies’ performance. The author notes that these decisions should be based on the modern methodological principles for assessing the complexsystems’ performance, taking into account the specific of the transport service process and the general requirements for evaluation methods. Materials and methods. The methods and tools of the quality management system, methods of system and the methods of structural and comparative analysis are used in the research. The main approaches to the task assessing effectiveness of the complex systems’ functioning are singled out, and their shortcomings, and the possibility of their application for the evaluation of performance in the theory of passenger motor transport are determined. Results. The author proposes to use the index normalization method to develop a methodology for assessing the performance of passenger enterprises, where the whole set of carefully selected indicators in accordance with accepted standards is converted from absolute values to relative ones. In accordance with it, the tasks and stages of subsequent research are defined. The article presents the classification model of the basic system formation of performance indicators and the functional scheme of their grouping for the subsequent indicators’ ranking by significance within each of the four groups. Discussion and conclusion. The author concludes that the index rationing method could be used for urban public transportation terms. Systematized enterprises’ indicators should be ranked in order of importance, first of all for the passenger, then for the department of transport, and only then for the enterprise, because efficiency in market conditions is not only a good financial result, but also the enterprise competitiveness for the quality of services and the amount of subsidies.